The effect of capital structure on the financial performance of companies listed on the Algerian stock exchange: Case of the Saidal group - Boussiki, Halima (Finance and Business Economies Review, 2023)
The present study aims to shed light on the impact of capital structure determinants on the financial performance of a public economic firm listed on the Algerian Stock Exchange, represented by the Saidal Group, during the period from 2010 to 2021. Furthermore, the study relied on the financial statements (balance sheet and income statement table) published on the official website of the stock exchange to collect the financial data of the firm. In pursuance of this aim, three multiple models were estimated in which dependent variables expressing financial performance were represented in each of the return on assets (ROA), return on equity (ROE), and earnings per share (EPS), while the independent variables expressing the determinants of the capital structure were represented in each of the ratio of medium and long-term debt to total assets (MLTDTA), the ratio of shortterm debt to total assets (STDTA), and the self-financing capacity (SFC). In addition to this, the control variables were used in the models to represent the liquidity and size of the firm, which was measured in the Neperian logarithm of its total assets. The study reached a set of results, the most important of which are the presence of a statistically significant positive relationship between the capital structure, as measured by the firm's self- inancing capacity, and the financial performance with its three indicators, as well as the existence of a statistically significant negative relationship between the ratio of medium- and long-term debt to total assets and financial performance. As for the ratio of short-term debt to total assets, it has a negative and statistically insignificant impact on both the return on assets and the return on equity, but also has a negative and statistically significant impact on earnings per share. In light of this, the study recommends that the firm should rely on internal financial sources rather than external financial sources to finance its various investments in order to improve its future financial performance